2013
DOI: 10.1111/aae.12012
|View full text |Cite
|
Sign up to set email alerts
|

The Neolithic in Arabia: a view from the south

Abstract: Maurizio Tosi alerted prehistorians to the significant evidence that Arabia followed its own path and with Serge Cleuziou has made a compelling argument about the distinctive social structure of Arabian complexity. After a decade of research and analyses based in Wadi Sana, Hadramawt, the RASA Project can offer a hypothetical scheme of the earliest social developments in highland southern Arabia. Domesticated animals came first; They were probably adopted or used by hunters still prizing wild game; Dedicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…In the following sections, we describe the fluting occurrences from Manayzah, as this site is dated and has a complete chaine opératoire for fluting (composed of 6 fluted pieces and 21 channel flakes). In addition, the fluted assemblage from a newly discovered site, Ad-Dahariz 2, will be discussed, as it is an exceptionally rich surface site where 46 Manayzah places fluting in South Arabia in a clear chronological framework, situating it in the South Arabian Neolithic [7,109,116]. This regional Neolithic tradition does not appear to https://doi.org/10.1371/journal.pone.0236314.g005…”
Section: First Discoveries In Arabiamentioning
confidence: 99%
See 1 more Smart Citation
“…In the following sections, we describe the fluting occurrences from Manayzah, as this site is dated and has a complete chaine opératoire for fluting (composed of 6 fluted pieces and 21 channel flakes). In addition, the fluted assemblage from a newly discovered site, Ad-Dahariz 2, will be discussed, as it is an exceptionally rich surface site where 46 Manayzah places fluting in South Arabia in a clear chronological framework, situating it in the South Arabian Neolithic [7,109,116]. This regional Neolithic tradition does not appear to https://doi.org/10.1371/journal.pone.0236314.g005…”
Section: First Discoveries In Arabiamentioning
confidence: 99%
“…We find evidence of highly skilled knappers at Manayzah, Ad-Dahariz and at other sites with fluted points in South Arabia. Individual prowess may be a means by which people mediated social relationships in this early Neolithic phase of Southern Arabia [116].…”
Section: Interpretation Of Fluting In South Arabiamentioning
confidence: 99%
“…Conversely, gene pools of other populations from the Arabian Peninsula seem to have been shaped mainly by demographic processes dating back to the Late Glacial period (Fernandes et al, ), thus having unlikely played a major role in the diffusion of −13,915 G adaptive allele. Furthermore, archaeological evidence suggest notable relevance of cattle domestication in the Yemeni societies at least since 8 kya (McCorriston, ; McCorriston et al, ), making the observed timeframe for the onset of LP genetic adaptation quite plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Such a scenario is slightly different for Southern Arabia, with whole mtDNA data suggesting that the current Yemeni mitochondrial landscape evolved mainly during the Neolithic, and even more recently, entailing again migrations from Western Eurasia, but also substantial differentiation of local haplogroups (Vyas et al, ). Moreover, archaeological evidence from the Wadi Sana in the Hadramaut Valley of central Yemen indicates that pastoralism was present in Southern Arabia by 8 kya, if not earlier (McCorriston, ). At the site of Shi'b Kheshiya in Wadi Sana, a monumental stone platform was excavated and showed 42 cattle skulls placed in on oval ring around a central skull.…”
mentioning
confidence: 99%
“…The Neolithic took on different forms in different regions, and in the challenging and often arid environments of Arabia, pastoralism and hunting were not exclusive options, but were instead often combined (e.g. McCorriston, 2013 ; McCorriston and Martin, 2009 ). As well as the findings from Shi’b Kheshiya mentioned above, changing social dynamics are visible in features such as the appearance of cemeteries and the construction of elaborate cairns, both of which have been argued to indicate increased attachment to particular places in the landscape and growing territoriality (e.g.…”
Section: Introductionmentioning
confidence: 99%